2005
DOI: 10.1152/physiolgenomics.00231.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific transcriptome responses in rats with early streptozotocin-induced diabetes

Abstract: The understanding of common and tissue-specific molecular alterations in diabetes, particularly at early stages, is limited and fragmental. In the present study, we systematically compared transcriptome responses in four important diabetic target tissues in rats with 2 wk of streptozotocin (STZ)-induced diabetes. At this stage of diabetes, the skeletal muscle exhibited the highest transcriptome sensitivity to the STZ treatment with nearly 17% of the transcriptome being altered (false discovery rate, 1.6%) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 39 publications
(42 reference statements)
9
58
1
Order By: Relevance
“…Mononuclear cell fractions were obtained from 8 -10 wk old male SS-13 real-time PCR machine (Applied Biosystems) and analyzed as described by Knoll et al (15). Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Mononuclear cell fractions were obtained from 8 -10 wk old male SS-13 real-time PCR machine (Applied Biosystems) and analyzed as described by Knoll et al (15). Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Renal regional tissues were collected and RNA was extracted as described previously (24,25,43). Real-time PCR analysis using the Taqman chemistry was performed as described previously (21,23,27). 18S rRNA was used as an internal normalizer.…”
Section: Methodsmentioning
confidence: 99%
“…The differentially expressed genes were annotated as described previously. 16,17,48,49 Real-Time PCR Real-time quantitative PCR was carried out with the same RNA used in the microarray studies using the ABI Prism 7900HT sequence detection system and SYBR Green reagents from Applied Biosystems (Foster City, CA) as described previously. 48,49 The sequences of the primers used in this study are shown in Table 3.…”
Section: Gene Expression Profilingmentioning
confidence: 99%